Конкурентоспособность библиотекарей на рынке труда (Библиосфера, 2010)
Article is devoted the analysis of competitiveness of library experts in the conditions of a modern society. The author offers the model of a competitive specialist, corresponding indexes are defined. The importance of professional skill of the expert under the conditions of social development complication is considered.